UJI AKTIVITAS ANTIOKSIDAN DAN TABIR SURYA KOMBINASI EKSTRAK KULIT BUAH PISANG KEPOK (Musa Paradisiaca Linn) DAN EKSTRAK KULIT BUAH ALPUKAT (Persea Americana Mill) - Wimpy Wimpy; Tri Harningsih; Whella Thalitha Larassati (Jurnal Ilmiah Manuntung, 2020)
The kepok banana peel extract (Musa paradisiaca Linn) and avocado peel extract (Persea americana Mill) contain alkaloids, flavonoids, saponins and steroids. There is a linear relationship between antioxidant activity and sunscreen capability. The stronger antioxidant activity,the better sunscreen capability will be. This study aims to determine antioxidant activity and sunscreen capability from the combination of kepok banana peel extract and avocado peel extract compared to it’s single form. This study was conducted with quota sampling. The preparation of ethanol extract from kepok banana peel and avocado peel were using maceration method with 96 % of ethanol. The study was started by collecting samples, making the extract with 96% ethanol solvent, then continue with phytochemical testing, antioxidant activity testing of kepok banana peel extract and avocado peel extract with variation ratio (1:0), (1:1), (1:2), (2:1), (0:​​1). Further tests including cream formulation, cream stability test and in vitro SPF value determination was also conducted. The result of IC50 determination from : kepok banana peel extract is 122,77, belongs to medium category; avocado peel extract is 11,50, belongs to very strong category; (kepok banana peel extract : avocado peel extract) (1:1) is 39,88, belongs to very strong category; (kepok banana peel extract : avocado peel extract) (1:2) : 25,31, belongs to very strong category; (kepok banana peel extract : avocado peel extract) (2:1) : 76,77, belongs to the strong category. The result of SPF measurement from the single form kepok banana is 16,21, belongs to ultra category; single form avocado peel is 21,21, belongs to ultra category; (kepok banana peel extract : avocado peel extract) (1:1) is 21,32, belongs to ultra category; (kepok banana peel extract : avocado peel extract) (1:2) is 21,52 belongs to ultra category; (kepok banana peel extract : avocado peel extract) (2:1) is 21,51, belongs to ultra category. The antioxidant activity from the variation ratio of banana peel extract and avocado peel extract (1:2) is stronger than the single form of banana peel extract, but it is weaker than the single form of avocado peel extract. The combination of kepok banana peel extract and avocado peel extract (1:2) has better sunscreen capability than it’s single form.